Studies on Consumer Motivation Among Users Of Fitness Services - Bartha, Éva Judit; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2018)
The rate of inactivity experienced world-wide is the cause of numerous health problems. The sedentary lifestyle of the population represents a great burden to a nation’s economy. The health indicators of Hungary are below the European average, not only those concerning physical activity, but also with respect to smoking, nutrition, and alcohol consumption [1]. In 2013, only 38% of the Hungarian population exercised regularly, while 62% rarely or never [2]. The diseases associated with inactivity represent a higher burden to the economy than the costs of raising the level of activity would be [3]. Based on previous studies, the motivating factors for leisure athletes in Hungary are the preservation of health, to increase physical strength, relaxation, recreation, the love of exercising, and stress management [4; 5]. The sports facilities available to a wide range of people, the fitness clubs offer the possibility to join regular sports activities, which is why it is necessary to examine the motivation behind the participation of athletes taking part in the trainings provided by fitness facilities. Many previous studies examined the goals of athletes and the motivational factors behind exercising, and came to the conclusion that trainings held in fitness rooms and at home are related to intrinsic motivational factors, while taking part in other sports activities are related to intrinsic motivational factors [6; 7]. The focus of my study are leisure athletes using the services provided by fitness clubs (753 people), of whom I evaluated the motivational factors behind taking part in trainings. The results show that the motivational factors driving consumers of fitness services show a ranking that is identical to those of other leisure athletes, with most of them taking part in fitness trainings in order to preserve their health, to improve physical strength, and for recreational purposes, while the improvement of physical appearance also plays an important role.